Risk factors for amyotrophic lateral sclerosis: A regional United States case‐control study. Issue 1 (18th October 2020) - Andrew, Angeline S.; Bradley, Walter G.; Peipert, Daniel; Butt, Tanya; Amoako, Kwadwo; Pioro, Erik P.; Tandan, Rup; Novak, John; Quick, Adam; Pugar, K. Doug; Sawlani, Komal; Katirji, Bashar; et al.
Abstract: Most amyotrophic lateral sclerosis (ALS) cases are considered sporadic, without a known genetic basis, and environmental exposures are thought to play a causal role. To learn more about sporadic ALS etiology, we recruited n = 188 ALS patients from northern New England and Ohio and matched controls 2:1 from the general population of the same regions. Questionnaires evaluated the association between a variety of lifestyle, behavioral (ie, hobbies and activities), and occupational factors and the risk of ALS, including the duration of time between exposure and ALS onset, and exposure frequency. Head trauma was associated with increased ALS risk (adjusted odds ratio [OR] 1.60 95% confidence interval [CI] 1.04‐2.45), with significantly greater effects for injuries occurring 10 or more years prior to symptom onset ( P = .037). ALS risk was increased for those reporting severe electrical burns (adjusted OR 2.86, 95% CI 1.37‐6.03), with odds ratios highest for burns after age 30 (OR 3.14), and for burns 10 or more years prior to symptom onset (OR 3.09). Hobbies involving lead were the most strongly associated with ALS risk (adjusted OR 2.92, 95% CI 1.45‐5.91). Exposures to lead 20 or more years prior to diagnosis had larger effect sizes compared to those occurring more recently. Holding a job in mechanics, painting, or construction was associated with ALS. The identification of these specific environmental factors associated with ALS highlight the need for future prospective and laboratory studies to assess causality, biological mechanisms, and find prevention or treatment opportunities.